Analisis Kerusakan Mesin CNC Lathe Dengan Metode Failure Mode And Effect Analysis (FMEA) (Studi Kasus Mesin CNC Lathe Fanuc Di Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau) - Risyandi, Danul; Susilawati, Anita; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to analyze the damage that occurs on the machine using the FMEA method (case study: CNC Lathe Fanuc machine at the Laboratory of Department of Mechanical Engineering Faculty of Engineering, University of Riau). The research method uses the Fault Tree Analysis (FTA) approach by identified an error tree to search for the roots of machine malfunction. Continue using FMEA method in the form of assigning weight rating of Saverity (S), Occurance (O), Detection (D) and Risk Priority Number (RPN) to become a proposed improvement to CNC Lathe machine. The results of the type of damage (Failure Mode) machine was the tool replacement system (movement M 06) failed / not completed. Causes of damage ( failure cause) machine were the motor components faults incorrecly writing program to command tool and faults of components of the automatic tool changger. The proposed improvements include checking and providing oil / lubricant on motor and tool changger components especially moving and rubbing components, repairing and replacing the motor and automatic tool changger components if needed, repairing the program deadlock, removing the M06 commands on the program, repair and replace the memory card if needed. Therefore, it is necessary to perform checks / maintenance periodically, not only when experiencing problems only.Keywords: Lathe CNC Machine, FMEA, FTA, RPN, Proposed improvemet